2011
DOI: 10.1016/j.ijfatigue.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Material dependence of multiaxial low cycle fatigue lives under non-proportional loading

Abstract: This study discusses evaluation of material dependence of multiaxial low cycle fatigue (LCF) to develop a suitable strain parameter for life estimation under non-proportional loading. It has been reported that fatigue lives are reduced accompanying an additional hardening under strain controlled non-proportional loading in which principal directions of stress and strain are changed in a cycle. Strain controlled multiaxial LCF tests using proportional and non-proportional strain paths were carried out using hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 12 publications
3
60
0
Order By: Relevance
“…torsion which depends on the difference in the deformation behavior due to different crystal structure (12) .…”
Section: Evaluation Of Low Cycle Fatigue Lifementioning
confidence: 99%
See 1 more Smart Citation
“…torsion which depends on the difference in the deformation behavior due to different crystal structure (12) .…”
Section: Evaluation Of Low Cycle Fatigue Lifementioning
confidence: 99%
“…The other method is to define α as the strain parameter in Circle to be equivalent to the strain parameter in Push-pull at the same N f based on life curves obtained in Push-pull and Circle tests. The later method usually gives better correlations of LCF lives of various materials (12) . For SUS316L, the two methods evaluate the value of α equivalently as α=0.9.…”
Section: Evaluation Of Low Cycle Fatigue Lifementioning
confidence: 99%
“…In strain controlled tests under multiaxial non-proportional loading, additional hardening due to non-proportional loading resulted from increase in interaction of activate slip systems which is related to additional damage have been reported [12]. In this study, stress and strain levels are relative small in which elastic deformation is dominant and directions of principal stress and strain are fixed into z-, θ-and r-directions.…”
Section: Fatigue Lifementioning
confidence: 74%
“…In recent literatures of multiaxial fatigue, it is reported that fatigue life evaluated by the Mises stress is overestimated [1][2][3][4][5][6][7][8] and the M magnitude depends on loading path [9][10][11][12][13][14][15][16]. In the multiaxial fatigue under non-proportional loading in which directions of principal stress and strain are changed in a cycle, it has been reported that fatigue lives are reduced accompanying with additional hardening which depends on both loading path and material [4][5][6][7][8][9][10][11][12][13][14][15][16]. In addition, Itoh et al presented a strain parameter for life evaluation under non-proportional loading considering the intensity of non-proportionality and the material dependency [12,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation